Convex Optimization - Differentiable Function



Let S be a non-empty open set in $\mathbb{R}^n$,then $f:S\rightarrow \mathbb{R}$ is said to be differentiable at $\hat{x} \in S$ if there exist a vector $\bigtriangledown f\left ( \hat{x} \right )$ called gradient vector and a function $\alpha :\mathbb{R}^n\rightarrow \mathbb{R}$ such that

$f\left ( x \right )=f\left ( \hat{x} \right )+\bigtriangledown f\left ( \hat{x} \right )^T\left ( x-\hat{x} \right )+\left \| x=\hat{x} \right \|\alpha \left ( \hat{x}, x-\hat{x} \right ), \forall x \in S$ where

$\alpha \left (\hat{x}, x-\hat{x} \right )\rightarrow 0 \bigtriangledown f\left ( \hat{x} \right )=\left [ \frac{\partial f}{\partial x_1}\frac{\partial f}{\partial x_2}...\frac{\partial f}{\partial x_n} \right ]_{x=\hat{x}}^{T}$

Theorem

let S be a non-empty, open convexset in $\mathbb{R}^n$ and let $f:S\rightarrow \mathbb{R}$ be differentiable on S. Then, f is convex if and only if for $x_1,x_2 \in S, \bigtriangledown f\left ( x_2 \right )^T \left ( x_1-x_2 \right ) \leq f\left ( x_1 \right )-f\left ( x_2 \right )$

Proof

Let f be a convex function. i.e., for $x_1,x_2 \in S, \lambda \in \left ( 0, 1 \right )$

$f\left [ \lambda x_1+\left ( 1-\lambda \right )x_2 \right ]\leq \lambda f\left ( x_1 \right )+\left ( 1-\lambda \right )f\left ( x_2 \right )$

$ \Rightarrow f\left [ \lambda x_1+\left ( 1-\lambda \right )x_2 \right ]\leq \lambda \left ( f\left ( x_1 \right )-f\left ( x_2 \right ) \right )+f\left ( x_2 \right )$

$ \Rightarrow\lambda \left ( f\left ( x_1 \right )-f\left ( x_2 \right ) \right )\geq f\left ( x_2+\lambda \left ( x_1-x_2 \right ) \right )-f\left ( x_2 \right )$

$\Rightarrow \lambda \left ( f\left ( x_1 \right )-f\left ( x_2 \right ) \right )\geq f\left ( x_2 \right )+\bigtriangledown f\left ( x_2 \right )^T\left ( x_1-x_2 \right )\lambda +$

$\left \| \lambda \left ( x_1-x_2 \right ) \right \|\alpha \left ( x_2,\lambda\left (x_1 - x_2 \right )-f\left ( x_2 \right ) \right )$

where $\alpha\left ( x_2, \lambda\left (x_1 - x_2 \right ) \right )\rightarrow 0$ as$\lambda \rightarrow 0$

Dividing by $\lambda$ on both sides, we get −

$f\left ( x_1 \right )-f\left ( x_2 \right ) \geq \bigtriangledown f\left ( x_2 \right )^T \left ( x_1-x_2 \right )$

Converse

Let for $x_1,x_2 \in S, \bigtriangledown f\left ( x_2 \right )^T \left ( x_1-x_2 \right ) \leq f\left ( x_1 \right )-f \left ( x_2 \right )$

To show that f is convex.

Since S is convex, $x_3=\lambda x_1+\left (1-\lambda \right )x_2 \in S, \lambda \in \left ( 0, 1 \right )$

Since $x_1, x_3 \in S$, therefore

$f\left ( x_1 \right )-f \left ( x_3 \right ) \geq \bigtriangledown f\left ( x_3 \right )^T \left ( x_1 -x_3\right )$

$ \Rightarrow f\left ( x_1 \right )-f \left ( x_3 \right )\geq \bigtriangledown f\left ( x_3 \right )^T \left ( x_1 - \lambda x_1-\left (1-\lambda \right )x_2\right )$

$ \Rightarrow f\left ( x_1 \right )-f \left ( x_3 \right )\geq \left ( 1- \lambda\right )\bigtriangledown f\left ( x_3 \right )^T \left ( x_1 - x_2\right )$

Since, $x_2, x_3 \in S$ therefore

$f\left ( x_2 \right )-f\left ( x_3 \right )\geq \bigtriangledown f\left ( x_3 \right )^T\left ( x_2-x_3 \right )$

$\Rightarrow f\left ( x_2 \right )-f\left ( x_3 \right )\geq \bigtriangledown f\left ( x_3 \right )^T\left ( x_2-\lambda x_1-\left ( 1-\lambda \right )x_2 \right )$

$\Rightarrow f\left ( x_2 \right )-f\left ( x_3 \right )\geq \left ( -\lambda \right )\bigtriangledown f\left ( x_3 \right )^T\left ( x_1-x_2 \right )$

Thus, combining the above equations, we get −

$\lambda \left ( f\left ( x_1 \right )-f\left ( x_3 \right ) \right )+\left ( 1- \lambda \right )\left ( f\left ( x_2 \right )-f\left ( x_3 \right ) \right )\geq 0$

$\Rightarrow f\left ( x_3\right )\leq \lambda f\left ( x_1 \right )+\left ( 1-\lambda \right )f\left ( x_2 \right )$

Theorem

let S be a non-empty open convex set in $\mathbb{R}^n$ and let $f:S \rightarrow \mathbb{R}$ be differentiable on S, then f is convex on S if and only if for any $x_1,x_2 \in S,\left ( \bigtriangledown f \left ( x_2 \right )-\bigtriangledown f \left ( x_1 \right ) \right )^T \left ( x_2-x_1 \right ) \geq 0$

Proof

let f be a convex function, then using the previous theorem −

$\bigtriangledown f\left ( x_2 \right )^T\left ( x_1-x_2 \right )\leq f\left ( x_1 \right )-f\left ( x_2 \right )$ and

$\bigtriangledown f\left ( x_1 \right )^T\left ( x_2-x_1 \right )\leq f\left ( x_2 \right )-f\left ( x_1 \right )$

Adding the above two equations, we get −

$\bigtriangledown f\left ( x_2 \right )^T\left ( x_1-x_2 \right )+\bigtriangledown f\left ( x_1 \right )^T\left ( x_2-x_1 \right )\leq 0$

$\Rightarrow \left ( \bigtriangledown f\left ( x_2 \right )-\bigtriangledown f\left ( x_1 \right ) \right )^T\left ( x_1-x_2 \right )\leq 0$

$\Rightarrow \left ( \bigtriangledown f\left ( x_2 \right )-\bigtriangledown f\left ( x_1 \right ) \right )^T\left ( x_2-x_1 \right )\geq 0$

Converse

Let for any $x_1,x_2 \in S,\left (\bigtriangledown f \left ( x_2\right )- \bigtriangledown f \left ( x_1\right )\right )^T \left ( x_2-x_1\right )\geq 0$

To show that f is convex.

Let $x_1,x_2 \in S$, thus by mean value theorem, $\frac{f\left ( x_1\right )-f\left ( x_2\right )}{x_1-x_2}=\bigtriangledown f\left ( x\right ),x \in \left ( x_1-x_2\right ) \Rightarrow x= \lambda x_1+\left ( 1-\lambda\right )x_2$ because S is a convex set.

$\Rightarrow f\left ( x_1 \right )- f\left ( x_2 \right )=\left ( \bigtriangledown f\left ( x \right )^T \right )\left ( x_1-x_2 \right )$

for $x,x_1$, we know −

$\left ( \bigtriangledown f\left ( x \right )-\bigtriangledown f\left ( x_1 \right ) \right )^T\left ( x-x_1 \right )\geq 0$

$\Rightarrow \left ( \bigtriangledown f\left ( x \right )-\bigtriangledown f\left ( x_1 \right ) \right )^T\left ( \lambda x_1+\left ( 1-\lambda \right )x_2-x_1 \right )\geq 0$

$\Rightarrow \left ( \bigtriangledown f\left ( x \right )- \bigtriangledown f\left ( x_1 \right )\right )^T\left ( 1- \lambda \right )\left ( x_2-x_1 \right )\geq 0$

$\Rightarrow \bigtriangledown f\left ( x \right )^T\left ( x_2-x_1 \right )\geq \bigtriangledown f\left ( x_1 \right )^T\left ( x_2-x_1 \right )$

Combining the above equations, we get −

$\Rightarrow \bigtriangledown f\left ( x_1 \right )^T\left ( x_2-x_1 \right )\leq f\left ( x_2 \right )-f\left ( x_1 \right )$

Hence using the last theorem, f is a convex function.

Twice Differentiable function

Let S be a non-empty subset of $\mathbb{R}^n$ and let $f:S\rightarrow \mathbb{R}$ then f is said to be twice differentiable at $\bar{x} \in S$ if there exists a vector $\bigtriangledown f\left (\bar{x}\right ), a \:nXn$ matrix $H\left (x\right )$(called Hessian matrix) and a function $\alpha:\mathbb{R}^n \rightarrow \mathbb{R}$ such that $f\left ( x \right )=f\left ( \bar{x}+x-\bar{x} \right )=f\left ( \bar{x} \right )+\bigtriangledown f\left ( \bar{x} \right )^T\left ( x-\bar{x} \right )+\frac{1}{2}\left ( x-\bar{x} \right )H\left ( \bar{x} \right )\left ( x-\bar{x} \right )$

where $ \alpha \left ( \bar{x}, x-\bar{x} \right )\rightarrow Oasx\rightarrow \bar{x}$

Advertisements